Análisis de la parrilla televisiva de Ecuador tv y sus distintas franjas horarias - Onofre Castro, Sinair Alcibiades (2019)
The following analysis work, collects all information regarding the process of preparing the programming grid of Ecuador TV, the state media that provides public information service to the Ecuadorian television audience since 2007. Through a tour of its facilities located in Quito, we find that this means of communication produces its own content with national talent and has added programs produced abroad by other public television stations with which they exchange audiovisual material. Ecuador TV devotes most of its programming grid to the education and orientation of the community and does not restrict content in its different time slots, since it does not use scenes of violence and sex that affect the psychological integrity of children of age. In the evidences of this work, we can observe how the staff of this Television station develops its activity in each space that is projected through its programming grid, the same one that is renewed each quarter, depending on the variety of programs that they add up